PENGARUH PENDEKATAN RME DAN AQ TERHADAP KEMAMPUAN KOGNITIF MATEMATIKA SISWA KELAS VII SMP - Yosheva, Novi; kamid, Kamid; Rusdi, Muhammad (Program Magister Teknologi Pendidikan Universitas Jambi, 2013)
The objective of this study is show how significant the influence of the use of RME approach and AQ to mathematics achievenment in SMP Negeri 2 Muaro Jambi. The study used exsperimental 2 Ã— 3 factorial design and was applied to two groups of this study is the second semester student in class VII SMP N 2 Muaro Jambi 2011/2012 which consist of 6 classes. Samples are taken randomly. Class VII-A is the experimen class and class VII-B is used for controlling. After learning shows that cognitif abilities differ siqnifikan both groups and the results of learning posttest experimental class Climber category earned an average yield learning (82) for the experimental class and average class learning outcomes for the control (68.36), which means that student cognitif abilities in learning RME approach is better than the student cognitif abilities using conventional approaches. Based on these results it can be concluded that the role of AQ climbers in the learning process by using the RME approach can improve cognitive ability math students. Keyword: Realistic Mathematics Education (RME) Approach, Adversity Quotient, Studentsâ€™ cognitive achievement